CompTIA Linux+ practice tests : exam XK0-005 - Suehring, Steve (Sybex, a Wiley brand, 2022)
This book provides practice questions for the CompTIA Linux+ certification Exam XK0-005. The questions are multiple choice, and the difficulty levels vary. The balance of questions closely mirrors the exam objective weighting in emphasis of certain technologies